2019
DOI: 10.1088/1478-3975/ab005f
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell variability of growth interactions within a two-species bacterial community

Abstract: Cell-cell interaction networks have been examined in many high diversity microbial communities using macroscale approaches. Microscale studies of multispecies communities are lacking and it remains unclear how macroscale trends scale down to small groups of cells. Experimental approaches using microfluidic devices have revealed heterogeneity in the behavior of single cells, however, this analysis has not been extended towards the variability of cell-cell interactions. Using a microwell device, we analyzed cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 80 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…Although they have not yet been employed for investigating algal-associated communities, the capability of microchambers for co-culture has been demonstrated in other microbial communities. For example, Guo et al studied single-cell variability in an array of microwells using a co-culture system of Escherichia coli and Enterobacter cloacae [27]. The microfluidic platform enabled them to investigate the heterogeneity of cell growth rate at the single-cell level.…”
Section: Modeling Microbial Community Organizationmentioning
confidence: 99%
“…Although they have not yet been employed for investigating algal-associated communities, the capability of microchambers for co-culture has been demonstrated in other microbial communities. For example, Guo et al studied single-cell variability in an array of microwells using a co-culture system of Escherichia coli and Enterobacter cloacae [27]. The microfluidic platform enabled them to investigate the heterogeneity of cell growth rate at the single-cell level.…”
Section: Modeling Microbial Community Organizationmentioning
confidence: 99%
“…Are there important consequences for populations when two rare phenotypes of different species interact? One recent experiment to report on this concept [90], examined the coupling of growth rates within small, mixed populations of E. coli and Enterobacter cloacae. Using a microwell device to create replicate groups containing only a few cells of each species, it was found that the mean and variability of growth rates was higher in co-cultures than single strain cultures.…”
Section: Single-cell Heterogeneity In Communicationmentioning
confidence: 99%
“…Most cellular properties are subject to random variability (noise) [1]- [3]. Although these fluctuations are traditionally studied in single-cell variables, such as protein levels, stochasticity also affects collective variables involving cell populations such as gene drift [4], [5], host invasion by pathogen cells [6], the survival of small groups to antimicrobial treatment [7], ecology of cell populations [8], size-based interactions [9] and metabolite production [10].…”
Section: Introductionmentioning
confidence: 99%